Reminiscence of a Forgotten Inheritage in Celvetiyye of Cyprus: The Building and Revival of the Mausoleum and Dervish Lodge of Kutup Osman Efendi in Magosa - Eyyamoglu, Mustafa; Pilehvarian, Nuran Kara (ISTANBUL 29 MAYIS UNIV & ISAM, 2019)
This article about the Kutup Osman Efendi Dervish Lodge, located outside of the walls of Famagusta in the Turkish Republic of Northern Cyprus, focuses on the changes the lodge went through especially before the nineteenth century based on the archival documents, engravings, maps and the recent literature. Atpazari Osman Fazli Efendi (1632-1691), who was among the most salient figures of Celvetiye brotherhood and who dispatched around 150 disciples, including the renowned Ismail Hakki Bursevi, to various parts of the Ottoman Empire, ended up being exiled to Famagusta where he deceased in 1691 because of his significant degree of intervention in politics in Istanbul. The tomb of this significant figure, who was buried in the outskirts of the Ottoman Graveyard located outside of the walls of the Famagusta, was eventually lost. Seyyid Mehmet Aga, also a member of the Celvetiye brotherhood and a head royal door-keeper, who was appointed to Cyprus as a tax officer (muhassil), found his tomb and built a mausoleum for him. Even though this mausoleum is mentioned in the endowment deeds, there is no mention of the masjid built next to it. Similarly, the fact that there was a dervish lodge in that location previously goes unnoticed. This article examines the mausoleum and the construction around it, the historical evolution of the area since the conquest of Cyprus, and it analyzes centuries-long archeological/cultural layers while observing the transformation of this previously Christian site into an Islamic one.
Keywords: Cyprus; Dervish Lodge of Kutup Osman Efendi; Ottoman Heritage; Turkish Culture in Cyprus; Ottoman Architecture of 19th Century in Cyprus; History; Asian Studies